Estimated Budget Impact of Adopting the Affordable Care Act's Required Smoking Cessation Coverage on United States Healthcare Payers. Issue 1 (January 2017) - Baker, Christine; Ferrufino, Cheryl; Bruno, Marianna; Kowal, Stacey
Abstract Introduction Despite abundant information on the negative impacts of smoking, more than 40 million adult Americans continue to smoke. The Affordable Care Act (ACA) requires tobacco cessation as a preventive service with no patient cost share for all FDA-approved cessation medications. Health plans have a vital role in supporting smoking cessation by managing medication access, but uncertainty remains on the gaps between smoking cessation requirements and what is actually occurring in practice. This study presents current cessation patterns, real-world drug costs and plan benefit design data, and estimates the 1- to 5-year pharmacy budget impact of providing ACA-required coverage for smoking cessation products to understand the fiscal impact to a US healthcare plan. Methods A closed cohort budget impact model was developed in Microsoft Excel® to estimate current and projected costs for US payers (commercial, Medicare, Medicaid) covering smoking cessation medicines, with assumptions for coverage and smoking cessation product utilization based on current, real-world national and state-level trends for hypothetical commercial, Medicare, and Medicaid plans with 1 million covered lives. A Markov methodology with five health states captures quit attempt and relapse patterns. Results include the number of smokers attempting to quit, number of successful quitters, annual costs, and cost per-member per-month (PMPM). Results The projected PMPM cost of providing coverage for smoking cessation medications is $0.10 for commercial, $0.06 for Medicare, and $0.07 for Medicaid plans, reflecting a low incremental PMPM impact of covering two attempts ranging from $0.01 for Medicaid to $0.02 for commercial and Medicare payers. Conclusion The projected PMPM impact of covering two quit attempts with access to all seven cessation medications at no patient cost share remains low. Results of this study reinforce that the impact of adopting the ACA requirements for smoking cessation coverage will have a limited near-term impact on health plan's budgets. Funding Pfizer Inc.